Biometrics System: An Overview - Neware, Shubhangi (International Journal of Computer Sciences and Engineering, 2025)
Use of biometrics system growing rapidly due to increase in demands for rigorous security in applications like national identity cards, border security, government benefits, network or computer login, time and attendance management, criminal investigation, passport control and access control. This paper is a review paper presenting introduction to biometrics technology comprising of its working, classification and operating modes. Different biometric modalities and related research work by researchers is also presented in this paper. Performance metrics for biometric system is also presented. This paper helps researchers to know the overall working of biometric system and research areas associated with different modalities in the field of biometrics.